Individual Wealth and Time Use : Evidence from Cambodia - Hasanbasri, Ardina; Kilic, Talip; Koolwal, Gayatri; Moylan, Heather (World Bank, Washington, DC, 2021)
A better understanding of how individual wealth and time use are linked—across paid, unpaid, and leisure activities —is important for targeting widespread gender inequalities in time allocation, as well as in accessing economic opportunities. The lack of reliable, individual-level data on asset ownership across different subpopulations, however, has limited discussions of these issues in the literature. Using a unique nationally representative survey from Cambodia, this paper shows that individual wealth, as measured through self-reported ownership of physical and financial assets, is significantly associated with time allocation to different activities. The role of asset ownership in time use is also stronger, particularly among women, vis-à-vis the competing proxies for socioeconomic status. Ownership of financial accounts, motorized vehicles, and mobile phones —all of which can improve access to networks, markets, and services—is associated with less time in unpaid work, and in some cases greater time in paid work, specifically among women in off-farm jobs. There are also distinct gender differences in how men and women shift their time away from leisure and childcare, highlighting the importance of social norms in choices over time use. The analysis highlights the utility of integrated, intra-household, individual-disaggregated data collection on asset ownership, time use, and employment in lower-income contexts.